Development Strategy of Kintamani Specialty Arabica Coffee Agro-Industry in Ulian Village, Kintamani, Bangli Regency - Ni Made Ayu Gemuh Rasa Astiti; Yohanes Parlindungan Situmeang; Gusti Agus Maha Putra Sanjaya; Ni Made Ayu Suardani Singapurwa; Ni Wayan Eka Manik Astini; I Gusti Bagus Udayana (Agriwar Journal, 2024)
Kintamani specialty Arabica coffee is a commodity that has a fairly high selling price. Bangli Regency is one of the regions in Bali Province that has good potential in developing the cultivation of Kintamani specialty Arabica coffee. This research aims to analyze and formulate the best strategy for developing Kintamani Specialty Arabica Coffee in Bangli Regency. The research methods used were internal factor evaluation (IFE) and external factor evaluation (EFE), internal-external matrix (IE), SWOT analysis, and SWOT analysis. The research results show that there are 32 internal factors and 55 external factors that make up the composition. IE analysis is in quadrant 1, with a progressive strategy recommendation. SWOT analysis shows that the strength factor has the highest weight of 0.412 with a consistency ratio of 0.035. The alternative strategies that have been formed are developing cultivation technology, carrying out continuous improvement in developing human resource skills for coffee farmers and production, carrying out continuous improvement in developing new products, creating a production timeline, analyzing and preparing forecasting marketing strategies, creating production SOPs to achieve product certification, increasing quantity, and quality of cultivation locations, increasing the number and quality of relationships with supply and marketing elements, increasing the number of promotional channels, and exercising control over production and marketing systems. This research concludes that the strategic priorities that must be carried out are progressive to developing government institutions, carrying out continuous improvement in developing human resource skills for Kintamani specialty Arabica coffee farmers and production, and analyzing and preparing forecasting marketing strategies.